The other blue: Role of sky in the perception of nature - Sztuka, Izabela Maria; Örken, Ada; Sudimac, Sonja; Kühn, Simone (Frontiers in Psychology, 2022)
Nature is frequently operationalized as greenery or water to estimate the restorativeness of the environment. Pursuing a deeper understanding of the connection between representation of naturalness and its relationship with restoration, we conducted an experiment aimed to investigate if the sky is perceived as an element of nature. The main goal of this study was to understand how composition of the environment guides people’s selection of sky as nature in an explicit task. Moreover, we investigated how the amount of visible sky determines this relationship. 105 participants participated in a novel explicit judgement task conducted online. In this task, we prepared a set of images trimmed out of 360-degree high dynamic range images. The images were classified according to two primary independent variables representing type of environment (4 levels: Nature, Some nature, Some urban, Urban) and horizon level (3 levels: Low, Medium, High). Each participant was asked to select, by clicking on the image, what they consider as “nature”. In addition, they were asked to judge images on five visual analogue scales: emotional response, aesthetic preference, feeling of familiarity, the openness of the space and naturalness. For analysis, images were segmented into 11 semantic categories (e.g. trees, sky, water) with each pixel being assigned one semantic label. Our results show that, sky is associated with selections of nature in a specific pattern. The relationship is dependent on the particular set of conditions that are present in the environment (i.e. weather, season of the year) rather than the type of the environment (urban, nature). The availability of sky on the image affects the selection of other nature labels with selections more likely when only a small amount of sky was available. Furthermore, we found that the amount of sky had a significant association with the naturalness rating of the whole image, but the effect was small. Our results also indicate that subjective selections of sky predict the naturalness better than trees and water. On the other hand, objective presence of trees and water has a stronger association with naturalness while objective presence of sky is significantly associated with naturalness.